2021
DOI: 10.1126/sciadv.abd9436
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 + neutrophils contribute to injury-induced infection susceptibility

Abstract: The underlying mechanisms contributing to injury-induced infection susceptibility remain poorly understood. Here, we describe a rapid increase in neutrophil cell numbers in the lungs following induction of thermal injury. These neutrophils expressed elevated levels of programmed death ligand 1 (PD-L1) and exhibited altered gene expression profiles indicative of a reparative population. Upon injury, neutrophils migrate from the bone marrow to the skin but transiently arrest in the lung vasculature. Arrested neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Furthermore, as compared with classical neutrophils and PMN-MSDCs, N2 TAN produce higher levels of chemokines but lower granules and ROS [ 75 , 76 ]. PD-L1-expressing neutrophils have been identified in cancer, infections, autoimmunity, and sepsis [ 77 , 78 , 79 , 80 , 81 ] and appear to be less prone to apoptosis than their PDL-1-negative counterparts [ 81 ]. Interestingly, these PDL-1-expressing neutrophils suppress the immune response by limiting activity of PD-1-expressing cells [ 77 , 78 , 79 , 80 , 81 ], culminating in either a protective or deleterious role according to the pathological context.…”
Section: Neutrophils: From Phagocytosis Sentinel To Immunoregulation ...mentioning
confidence: 99%
“…Furthermore, as compared with classical neutrophils and PMN-MSDCs, N2 TAN produce higher levels of chemokines but lower granules and ROS [ 75 , 76 ]. PD-L1-expressing neutrophils have been identified in cancer, infections, autoimmunity, and sepsis [ 77 , 78 , 79 , 80 , 81 ] and appear to be less prone to apoptosis than their PDL-1-negative counterparts [ 81 ]. Interestingly, these PDL-1-expressing neutrophils suppress the immune response by limiting activity of PD-1-expressing cells [ 77 , 78 , 79 , 80 , 81 ], culminating in either a protective or deleterious role according to the pathological context.…”
Section: Neutrophils: From Phagocytosis Sentinel To Immunoregulation ...mentioning
confidence: 99%
“…Thanabalasuriar et al. ( 63 ) reported the role of PD-L1 + neutrophils in mice with airway inflammation and found a protective effect of anti-PD-L1 antibody against inflammation. Our previous work presented that upregulation of neutrophil PD-L1 in inflammatory states can delay the apoptotic process through the PI3K/Akt pathway and consequently induce lung injury ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Thanabalasuriar et al. reported that blocking PD-L1 reduces airway inflammation and systemic treatment of injured animals with an anti-PD-L1 antibody prevented neutrophil accumulation in the lung and reduced susceptibility to infection ( 63 ). We verified the protective effect of anti-PD-L1 antibody against lung injury, the reduction of NET release and enhanced autophagy in vivo using a mice ARDS model.…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors have been well-validated, in human sepsis studies, to be upregulated on various immune cells, which leads to a dysregulated T cell response and subsequent immunosuppression ( 69 , 70 ). Similarly, burn murine models have exhibited increased PD-1, but this research is still relatively limited in terms of human thermal injuries and is non-existent in pediatrics ( 65 , 71 , 72 ). Within the present study, percent PD-1 expression on CD4+ lymphocytes was elevated for burn patients within the first 3 days of injury relative to HC ( Figure 2G ).…”
Section: Discussionmentioning
confidence: 99%